Radiographic and sonographic features, and histogram parameters of the liver and spleen in healthy Toco toucans (Ramphastos toco, Müller 1976) - da Silva, Jeana Pereira [UNESP]; Rahal, Sheila Canevese [UNESP]; Moresco, Anneke; Castiglioni, Maria Cristina Reis [UNESP]; de Campos Vettorato, Michel [UNESP]; Rolim, Luna Scarpari [UNESP]; Ichikawa, Ricardo Shoiti [UNESP]; Mamprim, Maria Jaqueline [UNESP] (Wiley, 2024)
This study aimed to evaluate radiographic and sonographic features, and histogram parameters based on grayscale ultrasound of the liver and spleen in healthy toco toucans. Fifteen adult toco toucans (Ramphastos toco), seven females and eight males, weighing approximately 650 g, were enrolled in the study. On the right lateral radiographic view, the liver was visualized in the midventral region of the coelomic cavity; ultrasonographically, the liver was located in the middle portion of the coelomic cavity in close relationship to the heart, and thoracic and abdominal air sacs. Two hepatic lobes were identified; the right lobe was larger than the left one. The spleen was visualized in 10 toco toucans on radiographs and only in eight toucans on ultrasound exams. The gallbladder was identified only on ultrasound. On the right lateral radiographic view, the spleen was visualized dorsal to the proventriculus and ventral to the lungs/air sacs as an oval shape. Ultrasonographically, the spleen was observed caudal to the liver, cranial to the proventriculus and craniodorsal to the ventriculus. There was no significant difference in spleen length for either radiographic or ultrasound measurements. The brightness intensity (BI) for mean gray level (G) and standard deviation of gray levels (SG) in the liver were 101.315 (± 16.170) and 12.453 (± 2.616), respectively. Mean G and SG levels in the spleen were 63.940 (± 18.321) and 7.494 (± 3.595), respectively. In conclusion, the sonographic features and histogram parameters indicated that the liver is more echogenic and heterogeneous than the spleen, which must be considered for diagnosing alterations in these organs.
Keywords: bird; imaging diagnosis; mean pixel intensity; ultrasonography